An energy-efficient mobile target detection scheme with adjustable duty cycles in wireless sensor networks. (2016) - Liu, Anfeng; Hu, Yanling; Chen, Zhigang
In this paper, an energy-efficient mobile target detection scheme with adjustable duty cycles (TDADCs) is proposed. TDADC has three advantages. First, it takes full advantage of the residual energy and improves the effective energy utilisation by increasing the sensing duty cycle of non-hotspot nodes. Secondly, the new scheme can significantly improve the overall probability of target detection. Thirdly, the notification transmission latency can be reduced by increasing the communication duty cycles of non-hotspot area. The problem of target detection can be addressed as an optimal problem trade-off between the target detection quality and network lifetime. A novel measurement framework called Weighted Quality of Target Detection (WQTD) is also proposed to measure the quality of target detection. Both theoretical and simulation results show that the proposed scheme significantly improved the probability of target detection, decreased the notification transmission latency and detection delay without reducing the network lifetime.